2020
DOI: 10.3390/cancers12082226
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Innate Immune Cells and Identifying Genes in Breast Cancer Microenvironment

Abstract: The innate immune system is the first line of defense against invading pathogens and has a major role in clearing transformed cells, besides its essential role in activating the adaptive immune system. Macrophages, dendritic cells, NK cells, and granulocytes are part of the innate immune system that accumulate in the tumor microenvironment such as breast cancer. These cells induce inflammation in situ by secreting cytokines and chemokines that promote tumor growth and progression, in addition to orchestrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 125 publications
0
27
0
Order By: Relevance
“…S9D). Interestingly, B-cell populations clustered closely with Natural Killer (NK) cells (mNEC12), cells known for playing an important role during mammary gland involution and breast tumorigenesis [82,83], and that are defined by genes like Killer Cell Lectin Like Receptor K1 (Klrk1) [84], Killer Cell Lectin Like Receptor D1 (Klrd1) [85], and Sialic acid binding Ig-like lectin H (Siglech) [86] (Fig. 4C, and Supplementary Fig.…”
Section: Outlining the Diversity Of Non-epithelial Mammary Resident Cell Typesmentioning
confidence: 98%
“…S9D). Interestingly, B-cell populations clustered closely with Natural Killer (NK) cells (mNEC12), cells known for playing an important role during mammary gland involution and breast tumorigenesis [82,83], and that are defined by genes like Killer Cell Lectin Like Receptor K1 (Klrk1) [84], Killer Cell Lectin Like Receptor D1 (Klrd1) [85], and Sialic acid binding Ig-like lectin H (Siglech) [86] (Fig. 4C, and Supplementary Fig.…”
Section: Outlining the Diversity Of Non-epithelial Mammary Resident Cell Typesmentioning
confidence: 98%
“…To understand the breast tumor microenvironment, preclinical studies have been shown that innate immune cells and the secreted cytokines have multifaceted roles that either promote or suppress breast tumor during disease progression or therapeutic responses. For instance, when upon interaction with tumor antigen via TLR or STING that primarily expressed on DCs and macrophages, these stimulated 46). This also leads to another opportunity of developing routine immunoprofiling analysis of breast tumors and patients, which should be matched to effective strategy during treatment planning and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted IL-12 and type I IFNs also can activate NK cells for lysing tumor cells. Meanwhile, breast tumor cells synthesize and secret TGFβ that directly or indirectly target various immune cells, which altogether mediate the immune escape for invasion and metastasis ( 46 ). This also leads to another opportunity of developing routine immunoprofiling analysis of breast tumors and patients, which should be matched to effective strategy during treatment planning and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The innate immune system originally serves as an initial border of defense against foreign invaders and alerts the adaptive immune system of impending attacks [ 7 ]. In TME, a large number of innate immune cells indirectly influences tumor progression by controlling T-cell functions [ 8 , 9 ]. For example, type-2 (M2) TAMs express multiple immunosuppressive and tumor promoting factors, such as prostaglandin E2, vesicular endothelial growth factor, and IL-10, leading to suppressed anti-tumor responses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%